CI-MBPT line strengths and atomic probabilities for some transitions of neutral iodine. (17th June 2020) - Filin, Dmytro; Savukov, Igor M; Colgan, James
Abstract: Iodine is a promising alternative to expensive xenon as a propellant for electric propulsion devices. Iodine optical spectroscopy is a valuable diagnostic tool for optimization of the iodine propellant. Recently, some measurements have been conducted with cells containing iodine plasma, and iodine atomic absorption at several wavelengths (911, 906, 206 and 1315 nm) was measured with a Ti:sapphire laser. Motivated by these experiments and future applications, we have calculated line strengths and atomic probabilities for the transitions between different types of 5s 2 5p 5, 5s 2 5p 4 6s, 5s 2 5p 4 6p and 5s 2 5p 4 5d states of atomic iodine, using configuration-interaction many-body perturbation theory. Since experimental transition data for atomic iodine are only available for a relatively small number of transitions, we also performed calculations for the bromine atom, to further validate our approach. We found good agreement between our theory and available experimental data for both elements in most cases. Therefore, we believe that our predicted line strengths and transition probabilities are quite reliable and will be useful for iodine spectroscopy.